PrPC regulates epidermal growth factor receptor function and cell shape dynamics in Neuro2a cells. (28th May 2013) - Llorens, Franc; Carulla, Patricia; Villa, Ana; Torres, Juan M.; Fortes, Puri; Ferrer, Isidre; del Río, José A.
Abstract The prion protein (PrP) plays a key role in prion disease pathogenesis. Although the misfolded and pathologic variant of this protein (PrPSC) has been studied in depth, the physiological role of PrPC remains elusive and controversial. PrPC is a cell‐surface glycoprotein involved in multiple cellular functions at the plasma membrane, where it interacts with a myriad of partners and regulates several intracellular signal transduction cascades. However, little is known about the gene expression changes modulated by PrPC in animals and in cellular models. In this article, we present PrPC‐dependent gene expression signature in N2a cells and its implication in the most overrepresented functions: cell cycle, cell growth and proliferation, and maintenance of cell shape. PrPC over‐expression enhances cell proliferation and cell cycle re‐entrance after serum stimulation, while PrPC silencing slows down cell cycle progression. In addition, MAP kinase and protein kinase B (AKT) pathway activation are under the regulation of PrPC in asynchronous cells and following mitogenic stimulation. These effects are due in part to the modulation of epidermal growth factor receptor (EGFR) by PrPC in the plasma membrane, where the two proteins interact in a multimeric complex. We also describe how PrPC over‐expression modulates filopodia formation by Rho GTPase regulation mainly in an AKT‐Cdc42‐N‐WASP‐dependent pathway. <boxed-text content-type="graphic" id="jnc12283-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text> In this study, we analyzed the PrPC‐dependent gene expression signature of neuroblastoma (N2a) cells after transient acute up‐regulation and down‐regulation of PrPC. We demonstrate that PrPC plays roles in proliferation and neuritogenesis through modulation of EGFR activity. This approach will give new insights into the molecular mechanisms by which PrPC regulates key cellular functions in cell physiology.